The Effectiveness of Education Using Snake and Ladder Media on Improving Knowledge and Attitudes Towards the Triad of Adolescent Reproductive Health at SMAN 6 Kota Madiun - Kharisma Restu Mawarni; Amarin Yudhana (Universitas STRADA Indonesia, 2025)
Adolescents are the future assets of a nation, the safety of the nation in the future lies in the hands of today's youth. However, along with the advancement of technology and information, lifestyle changes, and family structure in today's society, the emergence of adolescent issues is increasing. Such rapid changes make the position of adolescents very vulnerable to the negative impact of these changes. The condition of adolescents with various existing issues is called the adolescent reproductive health triad (Early Marriage, Pre-Marital Sex, Drugs and Terrorism). Therefore, it is important to conduct a deeper study on the effectiveness of snake ladder promotional media education on the knowledge and attitudes of adolescents in the adolescent reproductive health triad. This study aims to analyze the effectiveness of snakes and ladders promotional media on increasing knowledge and attitudes about the reproductive health triad at SMAN 6 Madiun City. this study also to analyze, identify and analyze the effectiveness of knowledge and attitude of adolescents about reproductive health triad through snakes and ladders media at SMAN 6 Madiun City, especially before and after the intervention of promotional media. The research method used was quantitative experimental design with one group pre test and pos test design, involving 179 selected respondents. Data were collected through questionnaires and analyzed using Wilcoxon test. The study showed that there was a significant positive relationship between knowledge and attitudes towards the effectiveness of snake ladder promotional media from the results of bivariate analysis using the Wilcoxon test showed an influence on the knowledge and attitudes of adolescents before and after intervention with a p-value of 0.000 < α (0.05). The implication of this study is the need for routine learning using promotional media. In addition, the management of supporting facilities needs to be more varied to increase adolescents' interest in learning.